Effects of Producers’ Subsidies on Estimating the Trade Balance in the Light of Free but Unfair Trade Relations of the EU - AKALPLER, Ergin (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
In this study effect of the support measures on the trade balance in the European Union’s (EU) is researched. It is evident, that the currently applied trade balance equation, which does not consider Producer Subsidy Estimate (PSE) of the OECD methodology -is the precise way of measuring the transfer from governments to producers in the EU, unfortunately prevents correct estimation of the trade balance. In this paper OECD data, Eurostat statistics and Agris database are considered for calculating old and new trade balances between 1990 and 2015.